HIPNORELAKSASI BERPENGARUH TERHADAP PENURUNAN TEKANAN DARAH PADA PENYANDANG HIPERTENSI PRIMER - Listiana, Vera; Subiyanto, Paulus; Lestari, Ratna (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Hypertension is a serious problem due to its high prevalence. Hypertension might be caused by life style changes such as smoking, obesity, physical inactivity and psychosocial stress. Almost 90% of hypertension prevalence is primary hipertension, with not-known causes. Hypertension can be treated with pharmacology and non-pharmacology approach. One of the applicable non-pharmacoogy methods is hypnorelaxation. Hypnorelaxation effects on the relaxation of the mind by producing endorphin through brain wave conversion. Suqsequently, blood pressure in patiens with hypertension will decrease. Objective: This study aimed to examine the influence of hypnorelaxation on the reduction blood pressure in patients with primary hypertension in Pedukuhan VI Sonosewu Ngestiharjo Kasihan Bantul Yogyakarta. Methods: The methods used in this study was quasy experimental with pre-and post-test in control group design. The subject was the patient with primary hypertension whose age 45-59 and 23 sampel were involved. The data collection was carried out through observation sheet, recording voice of hypnorelaxation and measurement of blood pressure. Results: There was a significant difference in systolic and diastolic blood pressure changes between intervention and control group. Conclusion: The study showed that there was influence of hypnorelaxation on blood pressure reduction in primary hypertension patients. Keywords: Hypnorelaxation, blood pressure